El factor de innovación fundamentado en la identidad ancestral aplicado en emprendimientos de diseño y de turismo comunitario - Burneo Villamagua, Jeamil (2018)
Analyze the potential of design with identity to generate a cultural product that is representative of Loja and that also promotes the development of community tourism in a site of high cultural interest and with specific characteristics favorable to the development of research. In the academic work, the design process seeks new design elements and products that are born fromthe iconographic research of the indigenous peoples that allow us to generate an element that identifies the archaeological site and that is transferred to the artisans of the sector. The experiences in the classrooms related to the process of creating patterns and design prototypes are analyzed in the development of the article, its preliminary validation of the market with the aim of generating its future production and manufacturing in different craft ranges that allow small businesses Produce correctly. We focused on the scope of the study on the site "Tambokocha", near the city of Loja, to determine some concretions regarding the influence of cultural revitalization related to the initial management of a community tourism sector in that place. We rescue the simultaneity of the conceptual theoretical work with the manufacturing of prototypes of the generated products, which have been presented in entrepreneurship events and exhibitions in the university and commercial instances, the apprentices of the activities are the conclusive ones regarding the viability and acceptance of production creative and its interference in activities related to culture.